The (im-)possibility of rational socialism: Mises in China's market reform debate - Isabella Weber (University of Massachusetts, Department of Economics, 2021)
This paper investigates the long first decade of reform in China (1978-1992) to show that Mises, in particular his initiating contribution to the Socialist Calculation Debate, became relevant to the reconfiguration of China's political economy when the reformers gave up on the late Maoist primacy of continuous revolution and adhered instead to an imperative of development and catching up. During the Cultural Revolution, Mao had rejected the notions of efficiency and rational economic management. In the late 1970s, the reformers under Deng Xiaoping's leadership elevated these notions to highest principle. As a result, Mises' critique that socialism could not achieve a rational economic order came to be debated throughout the 1980s and Chinese economists developed their own reading of Mises and the Socialist Calculation Debate. When Deng Xiaoping reinstated market reforms in the early 1990s after the Tiananmen crackdown, a history of thought review of the possibility of rational socialism and socialist markets helped to justify the Socialist Market Economy with Chinese Characteristics the official designation of China's economic system to this day.
Keywords: 330; Socialism; capitalism; market economy; Mises; China; comparative economic systems